Implementasi Kompilasi Hukum Islam dalam Pembagian Harta Warisan: Studi pada Masyarakat Nagori Sidotani Kabupaten Simalungun - Elpianti Sahara Pakpahan; Ardewifna Bakkara; Ahmad Nabil (Islam & Contemporary Issues, 2026)
The implementation of inheritance distribution based on the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) remains a challenge in many Muslim communities due to the coexistence of religious norms, local customs, and family-based decision-making practices. This study aims to analyze the implementation of KHI in inheritance distribution practices within the community of Nagori Sidotani, Bandar District, Simalungun Regency. This research employed a qualitative field research design involving [xx informants] selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation. Data validity was ensured through source triangulation and technique triangulation, while data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that inheritance distribution practices in the community have not been fully implemented in accordance with the faraidh provisions stipulated in KHI and are predominantly determined through family deliberation. Although this approach is intended to maintain social harmony, several cases indicate unequal inheritance allocation, particularly affecting women’s inheritance rights. The study identifies three main contributing factors: limited public understanding of Islamic inheritance law, insufficient legal dissemination by relevant institutions, and the influence of socio-cultural and economic conditions. These findings imply the need for continuous legal education and community outreach programs to strengthen the fair and effective implementation of KHI in inheritance practices.